2020
DOI: 10.1038/s42003-020-01435-w
|View full text |Cite
|
Sign up to set email alerts
|

PKN1 promotes synapse maturation by inhibiting mGluR-dependent silencing through neuronal glutamate transporter activation

Abstract: Abnormal metabotropic glutamate receptor (mGluR) activity could cause brain disorders; however, its regulation has not yet been fully understood. Here, we report that protein kinase N1 (PKN1), a protein kinase expressed predominantly in neurons in the brain, normalizes group 1 mGluR function by upregulating a neuronal glutamate transporter, excitatory amino acid transporter 3 (EAAT3), and supports silent synapse activation. Knocking out PKN1a, the dominant PKN1 subtype in the brain, unmasked abnormal input-non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Protein kinase C (PKC) has a long-established role in long-term potentiation and NMDA regulation(5658). Protein kinase N, a member of the PKC superfamily, directly interacts with AKT (the central node of our multi-omics network) and may have a specific role in synapse maturation(59, 60). The ERK/MAP kinase cascade regulates transcriptional events related to synaptic plasticity(61); and in addition to being a high-confidence differentially active kinase, ERK substrates were enriched among genes of interest, and ERK was the second most central node in our multi-omics network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinase C (PKC) has a long-established role in long-term potentiation and NMDA regulation(5658). Protein kinase N, a member of the PKC superfamily, directly interacts with AKT (the central node of our multi-omics network) and may have a specific role in synapse maturation(59, 60). The ERK/MAP kinase cascade regulates transcriptional events related to synaptic plasticity(61); and in addition to being a high-confidence differentially active kinase, ERK substrates were enriched among genes of interest, and ERK was the second most central node in our multi-omics network.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C (PKC) has a long-established role in longterm potentiation and NMDA regulation [51][52][53] . Protein kinase N, a member of the PKC superfamily, directly interacts with AKT (the primary hub of our multi-omics network) and may have a specific role in synapse maturation 54,55 . The ERK/MAP kinase cascade regulates transcriptional events related to synaptic plasticity 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that PKN1 promotes synapse maturation by inhibiting type I metabotropic glutamate receptor-dependent long term depression through regulation of excitatory amino acid transporter 3 (EAAT3) in area CA1 (Yasuda et al, 2020). Knockdown of PKN1 to 1/10th of WT levels results in immature synaptic transmission, more silent synapses and fewer spines with shorter postsynaptic densities in juvenile CA1 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrite arborization and spine density were quantified by an independent investigator. Dendritic spines were classified based on the spine length and spine head width, as follows: mushroom (with spine head, head width/length ratio > 0.5); thin (with spine head, length > 1.2 μm, head width/length ratio < 0.5); stubby (length < 1.2 μm, with spine head, head width/length ratio < 0.5; without head, not applicable); filopodia (without spine head, length > 1.2 μm) ( Llano et al, 2015 ; Yasuda et al, 2020 ). In addition to the four classical spine subtypes, we define varicosity as dendritic segments displaying varicose swellings (dendritic diameter > 2 μm) with spine loss ( Westrum et al, 1964 ; Isokawa, 1997 ; Swann et al, 2000 ; Maiti et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%